Pendekatan Tri Hita Karana dalam Pembelajaran IPS Kelas IV SDN Mengani untuk Membangun Harmoni Sosial dan Lingkungan - Pujiani, Nopi; Arnyana, Putu; Suja, Wayan (Jurnal Pendidikan Humaniora, 2024)
This study aims to explore the implementation of the Tri Hita Karana (THK) approach in Social Studies (IPS) learning in the fourth grade of elementary school to build social harmony and environmental awareness. The THK approach, focusing on three harmonious relationships—Parahyangan (the relationship between humans and God), Pawongan (the relationship among people), and Palemahan (the relationship between humans and nature)—is applied through various relevant learning activities. This research employs a qualitative method with data collection techniques including observations, interviews, and questionnaires. The results indicate that the THK approach significantly enhances students' social harmony and environmental awareness. This improvement is reflected in an increase in social harmony from 65% to 85% and environmental awareness from 60% to 82% after the method's application. Thus, implementing THK in Social Studies learning can be an effective approach to fostering students' harmonious and ethical character.